2008
DOI: 10.1016/j.radi.2007.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a method to support academic and professional competence throughout an undergraduate radiography programme

Abstract: Radiography degree programmes are coming under increasing pressure from the community to ensure that graduates have not only the necessary academic development but also the practice-based skills. This study aims to establish a method of monitoring students' progress towards, and ability to meet, academic and professional competences throughout a radiography programme. Methods Questionnaires were designed for students and academic staff to determine the stages and standards of progress of competence development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 54 publications
1
6
0
1
Order By: Relevance
“…A reliance on tradition and subjective experience has often been the norm for the profession. [21][22][23][24][25] This is also a finding among other health professions. 26,27 Health service research findings document a gap between best practice and actual clinical care.…”
Section: Evidence-based Radiography In Practicesupporting
confidence: 62%
“…A reliance on tradition and subjective experience has often been the norm for the profession. [21][22][23][24][25] This is also a finding among other health professions. 26,27 Health service research findings document a gap between best practice and actual clinical care.…”
Section: Evidence-based Radiography In Practicesupporting
confidence: 62%
“…Apparently, these three groups would be interrelated. The radiography education is the post-secondary education [25]. Only RTs over 50 years old would have more than 29 years of practice.…”
Section: Discussionmentioning
confidence: 99%
“…Th e MITs with diploma qualifi cations normally have extensive practical experiences. 23 A study suggested that this group of MITs tend to have a greater awareness of the importance of gonad shielding and more confi dence to use it properly. 14 Th is may explain their higher tendency to use shielding (question 2, Table 2).…”
Section: Discussionmentioning
confidence: 99%